The Effect of Job Satisfaction and Work Motivation on the Organizational Citizenship Behavior of Freelance Daily Worker Employees at the Secretariat of the DPRD of Solok Regency - Magdalena, Maria; Hamida, Annisa Fitri (Bina Bangsa International Journal of Business and Management, 2023)
Organizational Citizenship Behavior is the attitude of an employee that exceeds the duties and obligations that are not directly or explicitly recognized by the official reward system. This study aims to measure the magnitude of the effect of job satisfaction and work motivation on OCB in employees of the Solok Regency DPRD Secretariat Thl. The population of this study were Thl employees who worked at the DPRD secretariat which opened 62 respondents, using a saturated sampling technique. The data analysis technique used validity, reliability and TCR tests for questionnaires and multiple linear regression analysis for variable tests. The results showed that there was a positive and significant influence on work on the Organizational Citizenship Behavior (OCB) of Employees at the DPRD Secretariat of Solok Regency and there was a positive and significant influence on work motivation on the Organizational Citizenship Behavior (OCB) of employees at the DPRD Secretariat of Solok Regency. While the F test shows that the level of significant value is 0.000 < 0.050 and with a fcount of 362.605, it can be said that Ho is rejected and accepted, meaning work motivation (X2), and simultaneously has a positive and significant effect on Organizational Citizenship Behavior (Y).